2015
DOI: 10.1002/cyto.b.21331
|View full text |Cite
|
Sign up to set email alerts
|

CD180 overexpression in follicular lymphoma is restricted to the lymph node compartment

Abstract: These FCM data confirm the usefulness of CD180 in the accurate diagnosis of LPDs and emphasize the need to interpret this marker according to the origin of the sample. © 2015 Clinical Cytometry Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Recently, many studies have reported that the significantly different expression of CD43 in CLL and other mature B‐cell neoplasms could improve the differential diagnosis 13,19,20,35 . CD180 also had differential expression among mature B‐cell neoplasms and was identified to have a sensitivity of 77% and a specificity of 92% for the diagnosis of MZL 24‐26 . In CLL, CD180 could extend the proliferation and survival of B cells, 36 and was involved in susceptibility to fludarabine 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many studies have reported that the significantly different expression of CD43 in CLL and other mature B‐cell neoplasms could improve the differential diagnosis 13,19,20,35 . CD180 also had differential expression among mature B‐cell neoplasms and was identified to have a sensitivity of 77% and a specificity of 92% for the diagnosis of MZL 24‐26 . In CLL, CD180 could extend the proliferation and survival of B cells, 36 and was involved in susceptibility to fludarabine 37 .…”
Section: Discussionmentioning
confidence: 99%
“… 23 , 24 The differential expression of CD180 among chronic B‐cells lymphoproliferative diseases has been reported. 24 , 25 , 26 This study aimed to investigate the immunophenotyping data of patients with mature B‐cell malignancies, and whether a new combined score including CD43 and CD180 could improve the diagnostic value of CLL versus non‐CLL, particularly in CLL with CD5 or CD23 negativity.…”
Section: Introductionmentioning
confidence: 99%
“…Having a vaccine platform that is capable of acting on the first newly formed B cells to emerge from the BM may be a successful strategy for protecting these immunocompromised individuals. A potential concern of CD180 targeting transitional B cells is the activation of bystander B cells (61)(62)(63). Although in the B1-8 hi system this bystander activation was limited (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This issue contains two manuscripts examining CD180 in B cell lymphomas (9,10). The utility of CD180 is based just not on the presence or absence of this antigen, but also on the intensity of staining, similar to how CD200 is evaluated in B cell neoplasms (11).…”
Section: Cd180 In B Cell Lymphomasmentioning
confidence: 99%
“…They also show that CD180 is highly expressed on hairy cell leukemias (HCL). Also in this issue, Mestrallet and coworkers (10) examine CD180 expression in both the peripheral blood and lymph nodes from patients with follicular lymphoma (FL), chronic lymphocytic leukemia (CLL), mantel cell lymphoma (MCL), and marginal zone lymphoma (MZL), and well as from non-tumor-bearing controls. These authors again confirm the association of high levels of CD180 expression in the peripheral blood with MZL; however they extend these findings with the observation that CD180 expression is also high in the lymph nodes, but not peripheral blood, in cases of follicular lymphoma.…”
Section: Cd180 In B Cell Lymphomasmentioning
confidence: 99%